Ocena możliwości wdrożenia zintegrowanych systemów sterowania produkcją w małych i średnich przedsiębiorstwach - Kisiel, Piotr Grzegorz; Gara, Paweł (Wydawnictwa AGH, 2009)
Sector of small and medium-size companies is characterized with extreme development dynamics. In Polish conditions these are mainly family companies of minor capital. Commonly known and applied methods of the production control have been presented in this study. Analysis of implementation of such companies into small and medium-size company sector was also made.

Sektor małych i średnich przedsiębiorstw charakteryzuje się niesłychaną dynamiką rozwoju. W warunkach polskich są to głównie firmy rodzinne o niewielkim kapitale zakładowym. W artykule przedstawiono znane i stosowane metody sterowania produkcją. Poddano analizie możliwość ich wdrożenia w sektorze małych i średnich przedsiębiorstw.
Implementation of integrated production control systems in small and medium-size companies - the assessment
Automatyka
Keywords: production control systems; systemy sterowania produkcją; small and medium-size companies; małe i średnie przedsiębiorstwa